Frequency dependency of temporal contrast adaptation in normal subjects - Hohberger, Bettina; Roessler, Christopher W.; Jünemann, Anselm; Horn, Folkert; Kremers, Jan (Vision research, 2011)
The aim of this study was to determine the influence of temporal frequency of temporal contrast adaptation on contrast sensitivity in healthy subjects. Temporal contrast sensitivities (TCS) were measured monocularly in seven healthy subjects with a modified ERG full-field bowl stimulator at eight different test temporal frequencies (9, 15, 20, 25, 31, 37, 44, 51 Hz) using a two-alternative-forced-choice strategy. Before each presentation of the test stimulus, a 100% contrast adapting flicker stimulus was presented (frequencies: 9, 15, 20, 25, 31, 37, 44, 51, 100 Hz). At each adapting frequency, a complete set of TCSs was measured. All temporal contrast sensitivities decreased with increasing temporal frequencies. Adaptation led to a general temporal contrast sensitivity decrease. Largest adaptation effects were seen at an adaptation frequency of 25 Hz. Reduction of contrast sensitivity was significantly larger at 25 Hz adaptation than at 9 Hz adaptation (t-test of paired samples, Bonferroni corrected). The results of this study showed a general TCS decrease with the largest effect at an adaptation frequency of 25 Hz. This finding indicates that the contrast adaptation probably occurred in the magnocellular-pathway. In future clinical studies adaptation effects could be investigated in patients with reduced temporal contrast sensitivity.
EVALuna2:21010